Design of a cable-driven 2-DOF joint for dexterous robotic manipulator - Law, Wei Chuan. (2013)
Most aircraft components are compact and it is hard for human to visually check them. The method of observing an aircraft machine is to disassemble it to achieve inspection and then reassembling back. The process of disassembly and assembly is highly time consuming. Therefore, significant research has been done on snake-like robotic arm due to its ability to access confined and constrained spaces.